Analyst Recommendations and Financing Decisions of Public Listed Companies - Tiew, Wan Ying (2013)
This research is aim to examine the optimistic level of recommendations which provided by financial analysts in Malaysia. Therefore, this study focusing to find out the optimistic level, accuracy level and the market reactions in corresponding towards the recommendations which provided by independent analyst and sell-side analysts. The scope of research is focus on Bursa Malaysia and the target of sample research is the public listed companies which had announced equity financing issues. Firstly, to examine the difference between sell-side analysts’ recommendations and independent analysts’ recommendations, independent T-test was used to conduct the equality means test of recommendation between the two groups of analysts. The result indicates that there is no significant difference of recommendations from both groups of analysts, but the mean value shows that they tend to issue optimistic recommendations. Secondly, to examine the accuracy level of forecast error from sell-side analysts and independent analysts, independent T-test was used to conduct equality means test. The findings show that there is no significant difference between two groups of analysts. Lastly, to find out the market reaction towards the recommendations from both group of analysts, the average abnormal return (AAR) and cumulative average abnormal return (CAAR) was used to measure the response of investors. The results show that the investors respond positively towards hold recommendation from independent analysts and sell recommendation from sell-side analysts. Overall, the findings on this study suggest that the recommendations by both groups of analysts are considered optimistic and to have similar accuracy level of forecast errors, but lack of evidence to support that the main indicator is information asymmetry. Besides that, the market is actively respond to recommendations from analysts especially sell recommendation from sell-side analysts and hold recommendation from independent analysts.